SIMPLE EXPERIMENTS TO IMPROVE CHILDREN'S SCIENCE PROCESS SKILLS GUIDED PENANG LEARNING STUDIO INDONESIAN SOCIETY ORGANIZATION (PERMAI) - Khaleyla, Firas; Yuliani, Yuliani; Indana, Sifak; Susantini, Endang; Raharjo, Raharjo; Kuswanti, Nur (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
The Indonesian Community Association (PERMAI) is a nonprofit organization that supports Indonesian communities living in Malaysia. One of its educational programs is Sanggar Bimbing (SB) Permai, which provides access to education for Indonesian children who face difficulties obtaining formal education. In this program, students are introduced to Indonesian curriculum materials, including citizenship, history, culture, and the Indonesian language, as well as academic subjects such as basic science. However, limited facilities and teaching staff restrict the amount of material students receive. Therefore, an enrichment program on basic science was conducted through simple experiments to improve students’ science process skills. The program was implemented in three stages: preparation, implementation, and evaluation. The results showed a moderate improvement in students’ science understanding (N-gain = 0.53), very positive participant responses (average score = 4.38), and well-developed science skills, including observing, planning experiments, using tools and materials, and conducting experiments. Overall, the simple experiment activities received positive responses, although improvements are still needed to enhance their effectiveness and implementation according to students’ conditions.